Peningkatan Produktivitas Penulisan Buku Dosen melalui Pemanfaatan Artificial Intelligence Berbasis Etika Akademik - Syaharuddin Syaharuddin; Nuthya Rahmatin; Nursina Sari; Mardiyah Hayati; Johri Sabaryati; Dian Eka Mayasari Sri Wahyuni (Politeknik Penerbangan Indonesia Curug, 2026)
The use of Artificial Intelligence (AI) in academic book writing has the potential to increase the productivity and quality of lecturers' work, but requires a strong foundation of academic ethics so as not to violate scientific integrity. This Community Service activity aims to increase the productivity of book writing by lecturers at Muhammadiyah University Mataram through the use of AI based on academic ethics. The activity was attended by 22 lecturers from various faculties and was carried out in three stages, namely the preparation of AI-based book writing materials and modules, the implementation of training and workshops, and evaluation and reflection. The evaluation was conducted through direct observation and a Likert scale questionnaire covering seven indicators of writing competence and motivation. The evaluation results showed excellent achievements in all indicators, with a 90.91% understanding of AI concepts, 86.36% mastery of AI tools, 88.18% technical writing skills, 92.73% writing process efficiency, academic ethics comprehension of 90.91%, training material suitability of 92.73%, and an increase in writing motivation of 94.55%. This activity was effective in improving the technical competence and ethical awareness of lecturers in AI-based academic book writing.